Enantioselective deprotometalation of alkyl ferrocenecarboxylates using bimetallic bases. (24th November 2021) - Dayaker, Gandrath; Erb, William; Hedidi, Madani; Chevallier, Floris; Blot, Marielle; Gros, Philippe C.; Hilmersson, Göran; Roisnel, Thierry; Dorcet, Vincent; Bentabed-Ababsa, Ghenia; Mongin, Florence
Abstract : Our attempts to deprotometalate alkyl ferrocenecarboxylates enantioselectively by using chiral lithium–zinc or lithium–cadmium bases are reported. Abstract : The enantioselective deprotometalation of alkyl ferrocenecarboxylates (FcCO2 R) using mixed lithium-zinc or lithium-cadmium bases is described. By using FcCO2 Me as the substrate, chiral lithium alkyl-amidozincates prepared from exo -(α R )- or endo -(α S )- N -(α-phenylethyl)bornylamine (H- exo -born- R or H- endo -born- S ) were tested; the best results (27% yield and 62% ee in favor of the R P enantiomer) were obtained by using Bu2 ( endo -born- S )ZnLi in tetrahydrofuran (THF) at −30 °C before iodolysis. Due to the low compatibility of FcCO2 Me with alkyl-containing lithium zincates, 1 : 1 mixtures of lithium and zinc amides were tested. Chiral (H- exo -born- R or H- endo -born- S ) or/and achiral (lithium 2, 2, 6, 6-tetramethylpiperidide or lithium diisopropylamide) secondary amines gave good results, the best (81% yield and 44% ee in favor of the R P enantiomer) being obtained by using ( endo -born- S )3 ZnLi in THF at room temperature. Among other secondary amines also prepared and/or tested, commercial ( S, S )-bis(α-phenylethyl)amine (H-PEA- S ) proved promising. After optimization of the reaction conditions, the best enantioselectivity (26% yield and 80% ee in favor of the R P enantiomer) was observed by treating a THF solution of FcCO2 Me and Zn(PEA- S )2 with Li-PEA- S at −80 °C before iodolysis. That no reaction took place with cadmium instead of zinc suggests the formation of 'ate complexes upon treatment of Cd(PEA- S )2 by Li-PEA- S while Zn(PEA- S )2 and Li-PEA- S would rather work in tandem (Li-PEA- S as the base and Zn(PEA- S )2 as the in situ trap for the formed ferrocenyllithium). While FcCO2 Me, FcCO2 t Bu and FcCO2 iPr could be converted into their racemic 2-iodinated derivatives with a yield of 84 to 87% by employing LiTMP (2 equiv.) in the presence of ZnCl2 ·TMEDA (1 equiv.) as an in situ trap, their enantioselective deprotometalation rather required Li-PEA- S together with Zn(PEA- S )2 to produce the enantio-enriched derivatives with yields of 45–82% and 71% ee.